Partitioning of heat production in growing pigs as a tool to improve the determination of efficiency of energy utilization - Labussière, Etienne; Dubois, Serge; van Milgen, Jaap; Noblet, Jean (Frontiers in Physiology, 2013)
In growing pigs, the feed cost accounts for more than 60% of total production costs. The determination of efficiency of energy utilization through calorimetry measurements is of importance to sustain suitable feeding practice. The objective of this paper is to describe a methodology to correct daily heat production (HP) obtained from measurements in respiration chamber for the difference in energy expenditure related to physical activity between animals. The calculation is based on a preliminary published approach for partitioning HP between HP due to physical activity (AHP), thermic effect of feeding (TEF) and basal metabolic rate (FHP). Measurements with male growing pigs (mean body weight: 115 kg) which were surgically castrated (SC), castrated through immunization against GnRH (IC), or kept as entire male (EM) were used as an example. Animals were fed the same diet ad libitum and were housed individually in two 12-m3 open-circuit respiration chambers during six days when fed ad libitum and one supplementary day when fasted. Physical activity was recorded through interruption of an infrared beam to detect standing and lying positions and with force transducers that recorded the mechanical force the animal exerted on the floor of the cage. Corrected AHP (AHPc), TEF (TEFc) and HP (HPc) were calculated to standardize the level of AHP between animals, assuming that the ratio between AHPc and ME intake should be constant. Inefficiency of energy utilization (sum of AHPc and TEFc) was lower than the inefficiency estimated from the slope of the classical relationship between HPc and ME intake but was associated with higher requirements for maintenance. Results indicate that EM pigs had higher FHP but lower TEFc than IC and SC pigs. These results agree with the higher contents in viscera of EM pigs that stimulate their basal metabolic rate and to the reduced utilization of dietary protein to provide energy for maintenance energy requirements and fat deposition.